Moderasi Beragama Perspektif Maqashid Al-‎Shariah - Arifin; Chodir, Fatkul (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2024)
Religious moderation has gained prominence in response to escalating challenges of aith conflicts. Governments now recognize it as a fundamental pursuit essential for maintaining societal peace. Consequently, this study endeavors to demonstrate how religious moderation aligns with the principles of Maqasid al-Shariah, and remains pertinent to contemporary society. Employing a descriptive-analytical methodology rooted in library research, this study primarily relied on foundational texts supplemented by relevant articles. The focal point lies in the imperative role of religious moderation in fostering harmony among religious communities, and its resonance with Maqasid al-Shariah. The findings affirm that religious moderation, guided by Maqasid al-Shariah, underscores the need to strike a balance between religious freedom and societal responsibility. This serves as a crucial mechanism for thwarting extremism while championing peace, tolerance, and faith cooperation. Additionally, the study reveals that preaching within the framework of religious moderation transcends mere proselytization; it seeks to nurture inclusive attitudes, foster mutual respect, and prioritize communal welfare. In accordance with Maqasid al-Shariah, religious moderation underscores the significance of contextualizing religious teachings in social, cultural, and historical contexts.